Peran Guru Pendidikan Agama Islam Dalam Mengantisipasi Dampak Penggunaan Media Sosial Bagi Siswa Sekolah Menengah Pertama - Ismail Ismail (Institut Agama Islam Negeri Palopo, 2018)
This study aims to describe the existence of social media on student behavior and the inhibiting factors of PAI teachers in various social media at North Belopa State Middle School. This research is qualitative research that uses pedagogical, psychological, sociological, and theological normative approaches. Data sources are primary data sourced from principals, PAI teachers, and students through interviews, while data in the form of existing documents with research. The results of the study show that in the role of the teacher in using social media in junior high school students in the sub-district as follows: 1. Dutch Middle School students use social media as a place to show the outside world. Everyone is competing to display and make branding about the World World. There is nothing that can be done for others and 2. As for the PAI teacher's inhibitors in various social media at the North Belopa State Middle School, they are not working with teachers and parents in using social media. Community environment (association) association of students outside the school is also very large on the behavior and behavior of students in everyday life. Ineffective regulations made by schools.